PENYEDIAAN SARANA PENDUKUNG UNTUK MENINGKATKAN MINAT BACA REMAJA BEKASI - Chandra, Ricky; Sukada, Budi Adelar (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2024)
According from a study from United States, Indonesia is ranked 60th out of 61 countries measured by its population’s reading interest (Mikhael Gewati, 2016). One of the worst case existed in Bekasi, where only 10 percent of its teenagers has a sufficient reading interest. The main causes are the non-matching teenager’s character that is dynamic with the existing library’s characters which are enclosed and monotonous, as well as the obligation of text books usage, which makes them feel like they are being given additional “task” when reading other books (Quora, 2022). Both statements are proven after few teenagers are surveyed, where only 1 of 20 teenagers took interest in reading routinely. From this problem, hybrid-public library design is proposed, with programs such as reading analog and digital book, discussing, studying, eating together, watching video, playing games, and resting, to highlight the productive aspects of reading, not only done by just “staring texts”. After searching strengths and weaknesses of existing libraries in Bekasi, the location at Jl. Kimangun Sarkoro, RW.006, Bekasi Jaya, Kec. Bekasi Timur is recognized as the perfect place for the design. Since the surrounding buildings are low-rise, the library will be made with just 3-storey height, with the minimum required area is 5018,57 square meter. Architectural theme that will be applied has characters of “youth” which are flexible, unimpeded, with various material expressions and different from existing libraries. Keywords: reading facility; reading interest; teenager Abstrak Menurut sebuah studi yang berasal dari Amerika Serikat, Indonesia memasuki urutan ke-60 dari 61 negara yang diukur berdasarkan minat baca penduduknya (Gewati, 2016). Kasus yang parah berada di Kota Bekasi, di mana hanya 10 persen remaja yang tinggi minat bacanya. Penyebab utamanya adalah ketidaksesuaian karakter remaja yang dinamis dengan karakter sarana baca eksisting yang tertutup dan monoton, serta kewajiban penggunaan buku pelajaran, yang membuat mereka seperti diberi “tugas” tambahan saat membaca buku lain (Quora, 2022). Kedua hal ini terbukti setelah beberapa remaja di survei, dimana hanya 1 dari 20 anak remaja minat membaca secara rutin. Dari masalah ini, diusulkan perancangan sarana pustaka umum hibrida dengan program membaca buku analog dan digital, diskusi, belajar, berkumpul sambil makan, nonton video, bermain, dan istirahat, untuk menonjolkan aspek produktif dari membaca, yang tidak hanya sekedar “melihat teks”. Setelah menelusuri kelebihan dan kekurangan sarana pustaka eksisting di Bekasi, didapat lokasi Jl. Kimangun Sarkoro, RW.006, Bekasi Jaya, Kec. Bekasi Timur sebagai tempat yang tepat untuk rancangannya. Karena bangunan sekitar bertingkat rendah, maka sarananya akan dibuat setinggi 3 lantai saja, dengan luas yang dibutuhkan minimal 5018,57 meter persegi. Tema arsitektur yang digunakan berkarakter “youth” yang fleksibel, leluasa, dengan ekspresi material yang beragam dan berbeda dari sarana pustaka eksisting.